Potential of Students to Become Entrepreneurs in the Chemical Industry - Sebastian Walther; Stephan Haubold; Renata Dobrucka (MDPI AG, 2024)
Chempreneurs are revolutionary entrepreneurs who have been trained at a chemistry faculty. They are expected to find innovative solutions for current challenges to the chemical industry, such as sustainability. Innovative chemical entrepreneurship is the art of commercialising innovations from chemistry for a broad audience outside the classroom. Innovative ideas that are implemented with societal relevance offer the potential for individuals/graduates to generate income and promote the economy, thus offering students the opportunity to lay the foundation for a career with innovations developed in class. The probability of a German chemistry student founding a company is 54% lower than for the average German student. Previous studies show the potential effects of social capital, the subjective norm, motives and barriers for chemistry students in Germany. In this study, we tested these hypotheses by implementing entrepreneurship education. Two surveys, one before class and one with a one-week delay, were conducted with first- and third-semester chemistry bachelor students at the Fresenius University of Applied Sciences in Idstein, Germany. We conducted the surveys to understand how students view chemistry career opportunities through entrepreneurship and how to change this mindset. Finally, we propose a pedagogy to introduce/expand entrepreneurship in chemistry and discuss approaches for future research.